1998
DOI: 10.1021/ja982385f
|View full text |Cite
|
Sign up to set email alerts
|

Relation between the Structure and Spectroscopic Properties of Blue Copper Proteins

Abstract: The electronic spectra of three rhombic type 1 blue copper proteins, nitrite reductase, pseudoazurin, and cucumber basic protein, have been studied by ab initio multiconfigurational second-order perturbation theory (the CASPT2 method). The six lowest excitations have been calculated and assigned with an error of less than 1800 cm-1. The singly occupied orbital in the ground-state forms a strongly covalent antibond between the copper ion and the thiolate group of the cysteine ligand with a mixture of σ and π ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
246
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(265 citation statements)
references
References 37 publications
17
246
2
Order By: Relevance
“…7,[14][15][16][17][18][19][20] However, there has been less attention on small molecules that incorporate the copper-cysteine bond. Ryde et al have studied the structure and reorganization energy of small models of the copper cysteine bond, including CuSH 0/+ and [Cu(imidazole-CH 3 ) 2 (SC 2 H 5 (CH 3 SC 2 H 5 )] 0/+ , using a number of theoretical methods including density functional theory (DFT) with the B3LYP exchange-correlation functional, perturbation theory and coupled cluster theory.…”
Section: Introductionmentioning
confidence: 99%
“…7,[14][15][16][17][18][19][20] However, there has been less attention on small molecules that incorporate the copper-cysteine bond. Ryde et al have studied the structure and reorganization energy of small models of the copper cysteine bond, including CuSH 0/+ and [Cu(imidazole-CH 3 ) 2 (SC 2 H 5 (CH 3 SC 2 H 5 )] 0/+ , using a number of theoretical methods including density functional theory (DFT) with the B3LYP exchange-correlation functional, perturbation theory and coupled cluster theory.…”
Section: Introductionmentioning
confidence: 99%
“…In a study on a loop mutant of Amicyanin, a more limited temperature dependence was observed and assigned to the Boltzmann population of two electronic minima (25). In density functional theory (DFT) studies with a B3LYP hybrid functional, Ryde and coworkers predicated two minima, one similar to the blue copper site and a second similar to the green copper site at comparable energy (26). However, this depends on the functional and amount of HartreeFock mixing (5).…”
mentioning
confidence: 99%
“…The electronic structure of the blue copper site of plastocyanin has been studied extensively during the last decades both by experimental approaches (5,16,17,38) and quantum chemical calculations (5,10,(25)(26)(27)47). It was found that the unpaired electron spin density is located predominately at the atomic orbitals of the four atoms in the trigonal NNS-plane, i.e., the copper atom, the Cys S ␥ ligand, and the two aromatic His N ␦ ligands (5,16,17,(25)(26)(27)30), whereas the electron spin density at the Met S ␦ atom and the Cys H ␤ is small (26)(27)(28)38). Yet, it was found recently (31) that also the latter orbitals must be included in the description of the unpaired electron spin density to obtain a reliable prediction of the paramagnetic relaxation of the protons close to the copper site.…”
Section: Distribution Of the Unpaired Electron Spin In Plastocyaninmentioning
confidence: 99%
“…Because the paramagnetic restraints are derived from the relaxation rates of nuclei close to the metal site, the point dipole approximation of the electron spin fails and a description of the paramagnetic relaxation that takes the electron delocalization into account must be used (37). Therefore, the approach requires knowledge of the distribution of the unpaired electron spin, which can be obtained experimentally by x-ray absorption spectroscopy (16, 17), electron nuclear double resonance (38), paramagnetic NMR (28-31) spectroscopy, or theoretically by quantum chemical calculations (5,(25)(26)(27). The blue copper protein, plastocyanin from Anabaena variabilis (A.v.…”
mentioning
confidence: 99%
See 1 more Smart Citation